Effectiveness of Blended Learning on Academic Achievement in English among Secondary School Students of Gaya (Bihar) - Ms. Priyanka; Dr. Pawan Kumar (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
A significant amount of the traditional face-to-face teaching has been replaced by instructional strategies like blended learning, which can combine in-person and computer-mediated education. The purpose of this paper is to review and analyze earlier research on blended learning environments and how effective they are in enhancing the learning process. This paper has studied a number of cases that demonstrate how blended learning has improved students’ academic achievement and attendance rates, among other things. However, it’s important to keep in mind that depending only on blended learning could has its own limitations. Higher education establishments must provide careful consideration to each student’s different learning needs as well as their opinions regarding blended learning. When appropriate, higher education institutions may think about providing students the option to enroll in fully face-to-face or blended learning. Teachers should carefully plan their lessons to include a variety of expressive and engaging mediums in order to scaffold and assist students as they create their own blends. Students who experienced blended learning showed high levels of motivation, utility, and enjoyment, which influenced their attitude toward learning.